The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1755-1315/421/3/032017
|View full text |Cite
|
Sign up to set email alerts
|

Whey beverage with collagen hydrolysate from salmon skin and feijoa

Abstract: The article focuses on the development of a functional beverage produced from cheese whey and collagen hydrolysate being wastes of dairy and fishing industries. Fish collagen hydrolysate was hydrothermally extracted from salmon skin. Further, the sample was cooled, frozen and vacuum freeze dried. Collagen content in the obtained hydrolysate was equal to 37,5%. The hydrolysate was added to the whey beverage in the dose of 0,25%, 0,5%, 0,75% and 1%. In order to reduce the smell and taste of fish, 0,5% of feijoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Additionally, approximately 22% of its content is made up of the fatty acids palmitic acid and oleic acid. FW is an important source of by-products (proteins and amino acids, collagen and gelatin, oil and several enzymes) used in several fields and the food industry a functional ingredients [ 164 , 165 , 166 , 167 ]. Some studies have demonstrated the use of by-products obtained from FW in beverages with functional properties such as antioxidants against superoxide, ABTS and DPPH radicals and antimicrobial activity [ 168 , 169 , 170 ].…”
Section: Food Waste As An Ingredient For the Preparation Of Functiona...mentioning
confidence: 99%
“…Additionally, approximately 22% of its content is made up of the fatty acids palmitic acid and oleic acid. FW is an important source of by-products (proteins and amino acids, collagen and gelatin, oil and several enzymes) used in several fields and the food industry a functional ingredients [ 164 , 165 , 166 , 167 ]. Some studies have demonstrated the use of by-products obtained from FW in beverages with functional properties such as antioxidants against superoxide, ABTS and DPPH radicals and antimicrobial activity [ 168 , 169 , 170 ].…”
Section: Food Waste As An Ingredient For the Preparation Of Functiona...mentioning
confidence: 99%